2017
DOI: 10.7150/thno.20745
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of Polymeric Hybrid Micelles to Overcome Lymphatic and Intracellular Delivery Barriers in Cancer Immunotherapy

Abstract: Poor distribution of antigen/adjuvant to target sites and inadequate induction of T cell responses remain major challenges in cancer immunotherapy because of the lack of appropriate delivery systems. Nanocarrier-based antigen delivery systems have emerged as an innovative strategy to improve vaccine efficacy. Here we present polymeric hybrid micelles (PHMs) as a simple and potent antigen/adjuvant co-delivery system with highly tunable properties. PHMs consist of two amphiphilic diblock copolymers, polycaprolac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 39 publications
0
40
0
Order By: Relevance
“…Additionally, LyP-1 micelles had the most efficacy against tumors in vitro. In a study by Li et al, micelles composed of two amphiphilic diblock copolymers, polycaprolactonepolyethylenimine (PCL-PEI) and PCL-PEG, were loaded with Trp2 peptide and CpG oligodeoxynucleotide as an adjuvant [167]. Different ratios of cationic PCL-PEI were used, and it was determined that 10% w/w PCL-PEI had the best distribution into the lymph nodes and efficacy after subcutaneous administration.…”
Section: Active Lymphatic Targeting Systemsmentioning
confidence: 99%
“…Additionally, LyP-1 micelles had the most efficacy against tumors in vitro. In a study by Li et al, micelles composed of two amphiphilic diblock copolymers, polycaprolactonepolyethylenimine (PCL-PEI) and PCL-PEG, were loaded with Trp2 peptide and CpG oligodeoxynucleotide as an adjuvant [167]. Different ratios of cationic PCL-PEI were used, and it was determined that 10% w/w PCL-PEI had the best distribution into the lymph nodes and efficacy after subcutaneous administration.…”
Section: Active Lymphatic Targeting Systemsmentioning
confidence: 99%
“…Cui et al investigated polyplex micelles loaded with genes encoding the tumor-associated antigens SART3, GM-CSF, and CD40L and demonstrated that these micelles when administered subcutaneously may be safe and effective for tumor immunotherapy [139]. Researchers manufactured polymeric hybrid micelles (PHMs) loaded with Trp2 and CpG, and these PHMs consisted of polycaprolactone-polyethylene glycol (PCL-PEG) and 10% (w/w) PCL-PEI and were proven to have the ability to deliver antigen and adjuvant to lymph nodes and stimulate the CTL response, thus effectively inhibiting tumor growth [140]. Luo et al prepared poly(ethylene glycol)-b-poly(L-lysine)-b-poly(L-leucine) (PEG-PLL-PLLeu) micelles coloaded with OVA and STAT3 siRNA and proved that these micelles downregulate the expression of STAT3 and promote the maturation of DCs, thus improving the therapeutic efficacy of tumor vaccines [141].…”
Section: Novel Biomaterials For Cancer Immunotherapy Lipid-based Biommentioning
confidence: 99%
“…Due to its unique properties, polycaprolactone (PCL) is one of the most widely used polymers. PCL is biodegradable, miscible with other polymers, nontoxic, and easy to crystallize (Li et al., 2017 ; Totaro et al., 2017 ). Copolymers of TPGS-b-PCL such as PCL plus d -α-tocopheryl polyethylene glycol 1000 succinate (TPGS) have been widely used to deliver antitumor drugs such as genistein and paclitaxel (Tang et al., 2014 ; Parikh et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%